Targeting the Audience: Video Games as War Propaganda in Entertainment and News - Ottosen, Rune (Bodhi: An Interdisciplinary Journal, 2010)
This article will discuss video war games as propaganda, and the possible impact of video games on war reporting in news broadcasting. It will analyse computer games based on real wars in the light of Steven Poole's approach to computer games as modern mass media, and of Johan Galtung's theory of peace journalism. I will also draw upon earlier works on the military-industrial complex, to understand how the new generation computer games emerged from research within the armed forces in order to develop training videos for military personnel (Held, 2000; Lenoir, 2000). DOI: 10.3126/bodhi.v2i1.2862 Bodhi Vol.2(1) 2008 p.14-41